Timing of gold mineralization in the Hutti gold deposit, Dharwar Craton, South India - Sarma, D.; McNaughton, Neal; Fletcher, Ian; Groves, D.; Mohan, M.; Balaram, V. (Society of Economic Geologists Inc, 2008)
The Hutti orogenic gold deposit, in the eastern Dharwar craton of South India, is located in a cuspate greenstone belt which is tectonically juxtaposed against tonalite-trondhjemite-granodiorite (TTG) basement on its western margin. The host rocks to gold mineralization are mafic and felsic volcanic rocks metamorphosed to the amphibolite facies. Mineralization is confined to nine, broadly parallel, quartz reefs within north-south– to north-northwest-south-southeast–trending shear zones that dip approximately 70° W. Six of these 2- to 10-mthick, boudinaged veins have been mined to a depth of over 810 m. Free gold occurs in the veins and alteration haloes and is spatially and temporally associated with quartz and disseminated pyrite and arsenopyrite which, in turn, are closely associated with hydrothermal monazite and xenotime in the biotite-plagioclase wallrock alteration around veins. Gold is considered to have been deposited during D2 to D3 deformation, broadly coincident with the emplacement of syntectonic granitoids. The history of volcanism, granitic magmatism, and gold mineralization is defined by U-Pb geochronology of magmatic zircons and hydrothermal monazite and xenotime. The felsic volcanic host rocks have a U-Pb zircon age of 2587 ± 7 Ma, about 40 m.y. older than the age of gold mineralization at 2547 ± 10 Ma determined from hydrothermal monazite. The syntectonic Kavital granitoid has a U-Pb zircon age of 2545 ± 7 Ma, which overlaps with the timing of gold deposition and is consistent with structural interpretations. The Ramagiri and Kolar gold deposits elsewhere in the Dharwar craton are considered to have a similar structural timing, and the Huttigeochronology suggests that gold mineralization occurred throughout the Dharwar craton some 80 to 120 m.y. later than the major peak of Late Archean world-class orogenic gold mineralization in most other Archean cratons.